2012
DOI: 10.1021/ie201976e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Induced Normal Force of Magnetorheological Elastomer under Compression Status

Abstract: The magnetic-field-induced normal force of magnetorheological elastomer (MRE) under compression status is studied in this paper. The influence of monotonic loading of the magnetic field, particle distribution, temperature, and cyclic loading of the magnetic field are investigated. The experimental results show that the normal force increases with increasing magnetic field and precompression force. For aligned MRE, the change of the magnetic-field-induced normal force is larger than that of isotropic MRE due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…In particular, the normal stress can reach to as high as 60.2 kPa when suddenly applying a 930 mT magnetic field. The magneto-induced normal stress change is 3.44 times larger than the maximum normal stress change (17.5 kPa) of silicone rubber based magnetorheological elastomer with 80 wt.% carbonyl iron particle in the previous report by Liao et al 13 It can also be found from Fig. 1 that the normal stress gets a sudden increase and then approaches to saturated values slowly when an external magnetic field is applied.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…In particular, the normal stress can reach to as high as 60.2 kPa when suddenly applying a 930 mT magnetic field. The magneto-induced normal stress change is 3.44 times larger than the maximum normal stress change (17.5 kPa) of silicone rubber based magnetorheological elastomer with 80 wt.% carbonyl iron particle in the previous report by Liao et al 13 It can also be found from Fig. 1 that the normal stress gets a sudden increase and then approaches to saturated values slowly when an external magnetic field is applied.…”
Section: Methodsmentioning
confidence: 49%
“…The normal stress of magnetorheological fluid under one-way shear and oscillatory shear has been studied experimentally by Jang et al 11 and Gong et al, 12 respectively. Magneto-induced normal force of magnetorheological elastomer under compression state was investigated by Liao et al 13 Magneto-induced normal stress plays important role in the applications of magnetorheological material, such as polishing device, clutch, magneto-valve, seal device and especially the stability control of some magneto-device. Motivated by the aforementioned researches, for the new versatile a The authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…[98] Synthetic rubber-based MREs received more attention than the natural rubber MREs since they have higher resistance to oil, better aging, and weathering as well as resilience over a wide temperature range. [50,[182][183][184][185][186][187][188] The supplements needed during the vulcanization process are basically the same as for natural rubber. [180,181] High temperature vulcanization (HTV) silicone rubber is included in this kind of synthetic rubber due to its identical manufacturing process.…”
Section: Matrix Elementsmentioning
confidence: 99%
“…styrene butadiene rubber [42], chloroprene rubber (CIIR) [43], Bromo butyl rubber (BIIR) [44], isobutylene-isoprene [39], cispolyisoprene [45], cis-polybutadiene [27,[46][47][48][49][50], acrylonitrile rubber [51][52][53][54], and ethylene-propylene rubber [53,54]. The magnetizable particles used for MREs are commonly provided by well-known chemical companies such as BASF (carbonyl iron, spherical shape, 1-20 microns) [52,[55][56][57], ISP (carbonyl iron, spherical) [40,[58][59][60], Hoganas (iron powder, irregular shape above 20 micron) [61,62], and Sigma-Aldrich (carbonyl iron/iron pentacarbonyl) [63][64][65]. Based on the MREs raw materials mapping, it can be inferred that the entire MREs specimens proposed since 1996 have utilized rubber compound and commercial iron particles.…”
Section: Introductionmentioning
confidence: 99%